Optimal Liquidation of Assets in the Presence of Personal Taxes: Implications for Asset Pricing: Discussion - Richard, Scott F. (Journal of Finance, 1980)
Scott F. Richard, Optimal Liquidation of Assets in the Presence of Personal Taxes: Implications for Asset Pricing: Discussion, The Journal of Finance, Vol. 35, No. 2, Papers and Proceedings Thirty-Eighth Annual Meeting American Finance Association, Atlanta, Georgia, December 28-30, 1979 (May, 1980), pp. 450-452